2009
DOI: 10.1201/9780203875445.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing based assessment of biophysical indicators for land degradation and desertification

Abstract: Desert ecosystems spanning moisture conditions from dry grasslands to barren hyper-arid landscapes are the largest terrestrial biome with more than 40% of the terrestrial landmass. Remote sensing data provide an efficient costeffective means to assess biophysical indicators of land degradation and desertification, providing that essential ecosystem properties can be monitored. We review the spectral characteristics of plants and soils that are detectable using optical sensors and methods to identify and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 150 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…However, extrapolating and upscaling findings from local scale field studies to relatively large areas remain ambiguous. Other studies have shown that ecological and biophysical factors influencing land degradation processes can be monitored and assessed through the analysis of remote sensing images, particularly those acquired from onboard satellite instruments (Haboudane et al 2002;Thiam 2003;Wessels et al 2004;Ustin et al 2005).…”
Section: Satellite Remote Sensing Of Land Degradationmentioning
confidence: 99%
“…However, extrapolating and upscaling findings from local scale field studies to relatively large areas remain ambiguous. Other studies have shown that ecological and biophysical factors influencing land degradation processes can be monitored and assessed through the analysis of remote sensing images, particularly those acquired from onboard satellite instruments (Haboudane et al 2002;Thiam 2003;Wessels et al 2004;Ustin et al 2005).…”
Section: Satellite Remote Sensing Of Land Degradationmentioning
confidence: 99%